2019
DOI: 10.1002/pbc.27927
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of denosumab therapy for low bone mineral density in childhood cancer survivors: A report of preliminary experience

Abstract: Background:In childhood cancer survivors, low bone mineral density (BMD) is a bone-related consequence. Efficacy of denosumab, an effective therapy for adult patients with osteoporosis, remains unclear in children. This study aimed to investigate denosumab therapy efficacy for low BMD in childhood cancer survivors. , we monitored lumbar BMD of children with cancer using dual-energy X-ray absorptiometry after completing chemotherapy with a 6month interval. For patients with low BMD, defined as height-adjusted Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Hypokalemia and hypophosphatemia observed in current work is also referred in other studies related to leukemia 29,30 . Although hypocalcemia and hypochloremia observed in our study are also shown by other studies on childhood leukemia 31,32 . Furthermore, work presented here showed elevated CRP level, which was also observed in other recent studies 33–35 …”
Section: Resultssupporting
confidence: 92%
“…Hypokalemia and hypophosphatemia observed in current work is also referred in other studies related to leukemia 29,30 . Although hypocalcemia and hypochloremia observed in our study are also shown by other studies on childhood leukemia 31,32 . Furthermore, work presented here showed elevated CRP level, which was also observed in other recent studies 33–35 …”
Section: Resultssupporting
confidence: 92%
“…This finding is also emphasized by our control cohort's mean age and sex distribution: Mean age was significantly greater in controls compared with the patient cohort, and the percentage of females in controls was [33][34][35]. Moreover, the monoclonal anti-receptor activator of nuclear factor κ B (RANK)-ligand antibody denosumab has shown promising results by reducing fracture risk and increasing BMD [36,37]. However, these results were observed in postmenopausal females undergoing breast cancer treatment and childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 63%
“…Huang et al. reported that denosumab is an available treatment for BMD reduction in pediatric cancer survivors [ 18 ]. We have also proven the efficacy and safety of denosumab in children and young adults with refractory osteoporosis [ 9 12 ], although there have been no reports on denosumab for Williams syndrome and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%